Synthesis, Characterization, and Biological Activity of Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II) Complexes of N-Thiophenoyl-N′-Phenylthiocarbohydrazide - M. Yadav; Debasis Behera (Journal of Chemistry)
Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II) complex of N-thiophenoyl -N′-phenylthiocarbohydrazide (H2 TPTH) have been synthesized and characterized by elemental analysis, magnetic susceptibility measurements, infrared, NMR, electronic, and ESR spectral studies. The complexes were found to have compositions [Mn(H TPTH)2], [Co(TPTH) (H2O)2], [Ni(TPTH) (H2O)2], [Cu(TPTH)], [Zn(H TPTH)], [Cd(H TPTH)2], and [Fe(H TPTH)2(EtOH)]. The magnetic and electronic spectral studies suggest square planar geometry for [Cu(TPTH)], tetrahedral geometry for [Zn(TPTH)] and [Cd(H TPTH)2], and octahedral geometry for rest of the complexes. The infrared spectral studies of the 1 : 1 deprotonated complexes suggest bonding through enolic oxygen, thiolato sulfur, and both the hydrazinic nitrogens. Thus, H2TPTH acts as a binegative tetradentate ligand. H2 TPTH and its metal complexes have been screened against several bacteria and fungi.